Bilateral Profound Visual Loss As a Consequence of Leukaemia – A Case Report - Raajini Devi K.; Safinaz MK.; Hazlita MI. (Department of Surgery, UKM Medical Centre, 2015)
An 18-year-old Malay gentleman was noted to have profound bilateral blurred vision for one month duration, associated with loss of weight, appetite, low grade fever and abdominal distension. Visual acuity on presentation was 6/60 on the right, counting finger on the left with no afferent pupillary defect. Anterior segments were unremarkable. Vitreous cells were occasional bilaterally. Fundus revealed multiple choroidal and sub-retinal Roth spots with areas of pre-retinal and intra-retinal haemorrhages, involving the macula in the left eye. Vessels were dilated and tortuous in all quadrants of the right eye. Many areas of capillary fall out at peripheral retina were demonstrated in fundus fluorescein angiogram. Further systemic and laboratory review confirmed the diagnosis of CML and chemotherapy was initiated. Both eye ischaemic retinopathy secondary to CML was confirmed and scatter pan retinal photocoagulation was performed bilaterally. Good improvement in vision noted during subsequent follow up to 6/24 on the right, 6/60 on the left. High levels of suspicion and accurate early recognition of fundus changes are vital in these types of cases to ensure the institution of prompt treatment.